A concept for improving the environment of the railway station area in the city of Spassk-Dalniy - Remizova Darya R.; Glatolenkova Ekaterina V. (Архитектон, 2023)
The article considers issues in the conservation of the architectural heritage of the Ussuri railroad (the historical name of the line from Vladivostok to Khabarovsk). The study is a part of a large research project on the architectural image of the homeland and, specifically, the image of the homeland in the Far East. Spassk-Dalniy has preserved wooden residential buildings and a few stone buildings. Overall, the area around the railway station has not changed much since the line was built. The main part of the article discusses a project proposal to renovate the environment of this area with possible prospects for including it in the tourist railway routes. The design solution proposed is a result of six months work. The main provisions of the concept were derived in the course of the on-site studies and surveys conducted in 2021 and 2022. Russian and foreign experiences in the renovation of industrial and railway heritage sites are reviewed. A brief historical overview of the station area is provided.